Measuring Roots 2011
DOI: 10.1007/978-3-642-22067-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Fine Root Turnover

Abstract: Fine roots constitute an interface between plants and soils and thus play a crucial role in forest carbon, nutrient and water cycles. Their continuous growth and dieback, often termed turnover of fine roots, may constitute a major carbon input to soils and significantly contribute to belowground carbon cycle. For this reason, it is of importance to accurately estimate not only the standing biomass of fine roots, but also its rate of turnover. To date, no direct and reliable method of measuring fine root turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 27 publications
(26 reference statements)
1
33
0
Order By: Relevance
“…The comparisons of three methods (sequential soil coring, ingrowth methods, and minirhizotrons) for estimating forest fine root production and turnover revealed that the measured results were similar [1,24]. With sequential coring methods, there were also three methods to calculate production and turnover (decision matrix, the max-min, compartment) and previous results showed that the decision matrix method could represent best the actual value [25].…”
Section: Statistical Analysesmentioning
confidence: 95%
See 1 more Smart Citation
“…The comparisons of three methods (sequential soil coring, ingrowth methods, and minirhizotrons) for estimating forest fine root production and turnover revealed that the measured results were similar [1,24]. With sequential coring methods, there were also three methods to calculate production and turnover (decision matrix, the max-min, compartment) and previous results showed that the decision matrix method could represent best the actual value [25].…”
Section: Statistical Analysesmentioning
confidence: 95%
“…They are responsible for nutrient and water acquisition from soil and it is widely recognized that fine roots play a significant role in the carbon and biogeochemical cycle in forest ecosystems [1]. It has been estimated that approximately one third of annual net primary productivity was consumed in fine roots due to the rapid growth and turnover rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to aboveground litterfall, the flux of root litter has eluded quantification, partly because roots – the ‘hidden half’ of the terrestrial biosphere – are more difficult to observe and study. In addition, different techniques used to quantify fine‐root turnover – ranging from 13 C labeling, tracing the 14 C bomb peak, sequential soil coring and ingrowth cores to root cameras (minirhizotrons) – have yielded widely contradictory estimates of root turnover (Trumbore & Gaudinski, ; Pritchard & Strand, ; Strand et al ., ; Lukac, ).…”
Section: Introductionmentioning
confidence: 99%
“…By separating fine roots into a shorterlived absorptive pool and a longer-lived transport pool, McCormack et al (2015) showed that fine root functionality can alter estimates of global net primary productivity by 30%. This work highlights our still-limited understanding of fine root functionality, the mechanisms underlying their lifespan and turnover, and how those traits respond to abiotic stress (Lukac, 2012;Tierney and Fahey, 2002;Guo et al, 2008). Fine root mortality during drought has been linked to increased root respiration and inhibited photosynthate transport to roots (e.g.…”
mentioning
confidence: 99%